2013
DOI: 10.1139/cjfr-2012-0374
|View full text |Cite
|
Sign up to set email alerts
|

Allometric equations for estimating canopy fuel load and distribution of pole-size maritime pine trees in five Iberian provenances

Abstract: Adequate quantification of canopy fuel load and canopy bulk density is required for assessment of the susceptibility of forest stands to crown fire and evaluation of silvicultural treatments aimed at reducing the risk of crowning. The use of tree biomass equations and vertical profile distributions of crown fuels provide the most accurate estimates of the canopy fuel characteristics. In this study, 100 pole-size maritime pine (Pinus pinaster Aiton) trees were destructively sampled in five different sites, cove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
13
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 39 publications
5
13
0
1
Order By: Relevance
“…As commonly found for branch components, the precision was lower, with R 2 values of respectively 0.65 and 0.7 for P. cooperi and P. durangensis. Similar R 2 values for branch biomass prediction are commonly reported in the literature (e.g., [11][12][13]49,[64][65][66]). Tree branches are widely acknowledged to be difficult to model [67].…”
Section: Resultssupporting
confidence: 85%
“…As commonly found for branch components, the precision was lower, with R 2 values of respectively 0.65 and 0.7 for P. cooperi and P. durangensis. Similar R 2 values for branch biomass prediction are commonly reported in the literature (e.g., [11][12][13]49,[64][65][66]). Tree branches are widely acknowledged to be difficult to model [67].…”
Section: Resultssupporting
confidence: 85%
“…This effect presumably arises from the increased shading of lower branches in dense stands. Similarly, upward-shifted foliage distributions are frequently reported for trees in subordinate social positions (e.g., Maguire and Bennett 1996;Gilmore and Seymour 1997;Mäkelä and Vanninen 2001;Garber and Maguire 2005;Jiménez et al 2013; but see Weiskittel et al (2009)). This is likely a similar plastic response of within-crown foliage distribution to light competition.…”
Section: Introductionmentioning
confidence: 65%
“…ELEV_MAX variable was positively correlated to canopy height (Andersen et al, 2005), so looking at table 4 one can say that, under the same under conditions, high severity fire tended to occur more frequently in lower (i.e younger) stands. Studies in maritime pine stands for the same area (Jimenez et al 2013, Fernandez-Alonso et al 2013, Gomez-Vazquez et al 2013 have shown that there is a positive correlation between mean stand height or dominant height and canopy base height (CBH). Thus, higher stands may have also higher CBH values and therefore, lower possibilities of crown fire occurrence.…”
Section: Discussionmentioning
confidence: 99%
“…That type of stand replacement fires means a challenge for fire managers: they pose an important risk to population and firefighting crews due to difficulty to suppress them. They also are a threat to forest production by removing much or the entire tree canopy in a particular area, and resulting in considerable C emissions (Jimenez et al 2013). They reset the successional and growth processes of stands and forests (Graham et al, 2004) and can change post-fire dominant vegetation type (Holden, 2009).…”
Section: Introductionmentioning
confidence: 99%